FAKTOR-FAKOR DOMINAN YANG MEMPENGARUHI CALON MAHASISWA UNAI UNTUK MEMILIH UNAI DAN PROGRAM STUDI DI UNAI - Albinur Limbong; Horasdia Saragih (TeIKa, 2017)
This paper is a result of a series of surveys conducted on the new students of Universitas Advent Indonesia (UNAI), batches 2014, 2015, 2016 and 2017, regarding the reasons of the students choosing UNAI to study. The purpose of the study is to see the dominant factors that influence the new students to choose UNAI and their preferred study programs. This information is expected to be a very important for the decision makers to make a strategic planning of how to achieve UNAI vision that in 2020 UNAI students will be 3000, increasing from around 2000 in 2017. The results show that there are three factors, namely: UNAI is a dormitory campus with religious programs (55.77%), UNAI has a good quality and discipline (25.57) and UNAI has student labor or working education program (17.40%), while the rest is because is near their house or other reasons (12.87%). There are three reasons for the new students to choose the preferred study program, firstly because they are interested or talented in the study program (53.60%), secondly the study program has good quality and easier to get job after graduation (33.5%) and the rest is there is other preferred study programs available in UNAI and their parents asked them to study in UNAI (12.85%). Another important factor for the new students to choose UNAI is because UNAI has a good accreditation level from government. 88.10% of the new students agree and even fully agree that the accreditation level of the preferred study program is very important factor for them to choose the study program. However, it is interested to study in the future why the adventist students in West Indonesia Union Missions (estimated to be around 80%) do not choose to study.